A comprehensive bibliometric analysis (2000–2022) on the mapping of knowledge regarding immunotherapeutic treatments for advanced, recurrent, or metastatic cervical cancer - Duan, Yuanqiong; Yang, Lin; Wang, Wenxiang; Zhang, Peixuan; Fu, Kaiyu; Li, Wen; Yin, Rutie (Frontiers in Pharmacology, 2024)
Despite extensive literature on therapeutic strategies for cervical cancer, a bibliometric analysis specifically focused on immunotherapy for advanced, recurrent, or metastatic (A/R/M) cervical malignancies remains unexplored. This study aims to address this gap by presenting a comprehensive overview that includes general characteristics, research focal points, the trajectory of evolution, and current emerging trends in this underresearched area.A systematic search was conducted using the Web of Science Core Collection (WOSCC) to identify articles related to A/R/M cervical cancer published between 2000 and 2022. Citespace and VOS viewer were the primary tools used to identify research focal points, intriguing future patterns, and to evaluate contributions and cooccurrences among authors, institutions, countries, and journals. 2 Results A total of 1,001 original articles were identified, involving 6,387 authors from 66 countries and 1,474 institutions, and published across 366 academic journals. The United States contributed most significantly. The most productive researcher was Van der Burg SH from Leiden University Medical Center. The International Journal of Cancer and Cancer Research were identified as the most productive and influential journals, respectively. Analysis of co-citation clusters highlighted 25 clusters, primarily focusing on potential predictive biomarkers, dendritic cell-based tumor vaccines, therapeutic HPV vaccinations, peptide-based cancer vaccines, tumor immune microenvironments, and adoptive cell transfer (ACT). The latest significant trends in A/R/M cervical cancer immunotherapy research included ACT, CAR-T, and immune checkpoint inhibitors (ICIs), as revealed by keyword and reference burst detection. Conclusion This pioneering study provides a detailed landscape of immunotherapy research in A/R/M cervical cancer. It underscores the importance of global collaboration, enriches our understanding of the immunology of A/R/M cervical cancer, expands on potential beneficiaries of immunotherapy, and explores clinical applications of various therapies, including therapeutic vaccines, adoptive cell transfer, and ICIs, particularly in combination with established treatments such as chemotherapy, radiotherapy, and targeted therapy.